INCOME DYNAMICS OF MICRO-TRADERS AMIDST CLIMATE CHANGE AND ECONOMIC PRESSURES: A QUALITATIVE STUDY OF MICRO-TRADERS IN KEMBANGBAHU DISTRICT, LAMONGAN REGENCY - Jessica Lia febriyanti; Muhammad Hafidh Nasrullah; Ariefah Sundari (International Journal of Multidisciplinary Reseach, 2026)
Climate change and economic pressures pose challenges to the business sustainability of micro-traders, primarily due to erratic weather patterns, rising raw material costs, and declining public purchasing power. These conditions cause fluctuations in the income of micro-traders in Kembangbahu District, Lamongan Regency, necessitating an examination of the influencing factors. This study aims to describe the income dynamics of micro-traders, analyze the impact of climate change and economic pressures on income, and identify the adaptation strategies employed by traders to sustain their businesses. The study employs a qualitative approach with a descriptive design. Data were collected through in-depth interviews, observation, and documentation involving micro-traders as key informants, and subsequently validated using source and technique triangulation. The results indicate that micro-traders' income fluctuates, influenced by climate change, which leads to a reduction in the number of consumers and disruptions in the distribution of goods. Furthermore, economic pressures manifesting as rising raw material prices, increased operational costs, and declining public purchasing power further reduce traders' profits. To sustain their businesses, traders implement various adaptation strategies, such as adjusting operating hours, diversifying products, cutting operational costs, and utilizing social media for marketing. The study concludes that climate change and economic pressures significantly impact the income dynamics of micro-traders. Therefore, government support is required through business capacity building, access to capital, and business digitalization. Future research is encouraged to expand the study area to obtain more comprehensive results.